2012
DOI: 10.1152/ajpendo.00231.2012
|View full text |Cite
|
Sign up to set email alerts
|

Activity restriction, impaired capillary function, and the development of insulin resistance in lean primates

Abstract: Insulin produces capillary recruitment in skeletal muscle through a nitric oxide (NO)-dependent mechanism. Capillary recruitment is blunted in obese and diabetic subjects and contributes to impaired glucose uptake. This study's objective was to define whether inactivity, in the absence of obesity, leads to impaired capillary recruitment and contributes to insulin resistance (IR). A comprehensive metabolic and vascular assessment was performed on 19 adult male rhesus macaques ( Macaca mulatta) after sedation wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 32 publications
1
36
0
Order By: Relevance
“…Animal and human studies have also demonstrated an association between impaired CBV response to insulin and impaired glucose homeostasis, thereby suggesting that impaired vascular responses contribute to IR (13,14,39,44). It has been shown that abnormal capillary responses occur very early in the course of IR in nonhuman primates produced by inactivity and in humans at the stage of obesity and mild to moderate IR (10,14). These observations have helped to understand how tissue perfusion influences glucose regulation, but they have not yet been translated into new therapies for IR or diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal and human studies have also demonstrated an association between impaired CBV response to insulin and impaired glucose homeostasis, thereby suggesting that impaired vascular responses contribute to IR (13,14,39,44). It has been shown that abnormal capillary responses occur very early in the course of IR in nonhuman primates produced by inactivity and in humans at the stage of obesity and mild to moderate IR (10,14). These observations have helped to understand how tissue perfusion influences glucose regulation, but they have not yet been translated into new therapies for IR or diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…A functional increase in CBV increases effective vascular surface area for not only glucose uptake but possibly also insulin transport into tissue (34). Augmentation of skeletal muscle perfusion in response to either insulin or glucose challenge is blunted in insulin resistance (IR) (10,13,14,44), suggesting that microvascular dysfunction contributes to impaired glucose homeostasis. Insulin-mediated capillary recruitment has been shown to involve production of nitric oxide (NO) (40,41), thereby establishing a potential link between endothelial IR, which is manifested by reduced phosphorylation of endothelial NO synthase (eNOS), and impaired flow response to insulin (24).…”
mentioning
confidence: 99%
“…While the root causes of insulin resistance are multifactorial, two of the major contributors are increased dietary fat and a sedentary lifestyle [1][2][3][4]. A defining feature of insulin resistance is impaired glucose disposal by the skeletal muscle, which is normally responsible for ~80% of insulin-mediated glucose uptake in the post-prandial state [5].…”
Section: Introductionmentioning
confidence: 99%
“…1-3 In humans and a wide array of species, contrast-enhanced ultrasound (CEU) has been used to demonstrate that limb skeletal muscle MBF and capillary blood volume (CBV) increase in response to carbohydrate challenge or physiologic hyperinsulinemia, 4-8 and that this response is abnormal in insulin resistance (IR) states. 7,9,10 CEU has also been applied to identify biologic mediators of the microvascular response to insulin which include nitric oxide (NO) and arachadonic acid-derived compounds. 7,11,12 In aggregate, CEU studies have supported the notion that microvascular dysfunction is not simply a consequence of IR, but also contributes to IR.…”
mentioning
confidence: 99%